KEMAMPUAN MEMBUAT KALIMAT PASIF SISWA KELAS XI JURUSAN TEKNIK JARINGAN TENAGA LISTRIK SMK NEGERI 2 PEKANBARU - Ery Desilawati; Maryam Kasnaria (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study aims to determine and explain the level of ability to make passive sentences of Indonesian class XIstudents Teknik Jaringan Tenaga Listrik SMK Negeri 2 Pekanbaru even semester in lesson year 2017/2018. Thetheory used, Alwi, et al. (2003) and Sinaga (2015) concerning the active and passive understanding of the sentencesconcerning three things, (1) kinds of predicate verbs, (2) subjects and objects, and (3) forms of verbs used; Sinaga(2015) about the sentence; Marhamah (2011) and Suhardi (2013) on the meaning of passive sentences and theircharacteristics; Sugiyono (2011) on descriptive research; and Razak (2005) on data analysis and scoring; The studywas conducted using tests making passive sentences and turning active sentences into passive sentences. Datasource 30 students. The results showed that the level of ability of students class XI Teknik Jaringan Tenaga ListrikSMK Negeri 2 Pekanbaru in making passive sentence is 65.19% in low category (R), which is disaggregated above(1) the level of ability to make passive predictive sentence predicate in 96%, high categorized (T), (2) the level ofability to make active sentences into passive sentences is 55.56%, low category (R), and make predictive predictionster- 44% predicate failed categorized (G). Thus, the ability of class XI students Teknik Jaringan Tenaga Listrik SMKNegeri 2 Pekanbaru make passive sentences of Indonesian language of 65.19%, low category (R).